Statina – touch interface engine - Huang, Jiesi. (2012)
Human-computer interface (HCI) technologies have been moving away from buttons and pointing devices towards more intuitive options, most notably the touch screen. Current touch screen technologies are costly, especially for large screens since special screens are used. In the STATINA project, an affordable touch screen option is presented as shock sensors are used to transform ordinary surfaces into touch screens.